2016
DOI: 10.1016/j.jadohealth.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Adolescent Interest in Receiving Adolescent Health Communication Information From Primary Care Clinicians

Abstract: Parents and adolescents want health care professionals to help them learn and talk about a wide range of adolescent health topics. Feasible primary care interventions that effectively improve parent-teen health communication, and specific adolescent health outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…Health care providers can be important partners with adolescents and with their parents or guardians in promoting healthy behaviors through a triadic approach (child, parent, and provider), whether working directly with adolescents or with their parents or indirectly through supporting a healthy parent-child relationship (54,55). One study examining parent-adolescent dyads found a significant correlation between parents and adolescents with regard to their desire for sexual health information from providers, suggesting that when adolescent patients have sexual health questions for providers, their parents might have those same questions as well (56).…”
Section: Therapeutic Partnershipmentioning
confidence: 99%
“…Health care providers can be important partners with adolescents and with their parents or guardians in promoting healthy behaviors through a triadic approach (child, parent, and provider), whether working directly with adolescents or with their parents or indirectly through supporting a healthy parent-child relationship (54,55). One study examining parent-adolescent dyads found a significant correlation between parents and adolescents with regard to their desire for sexual health information from providers, suggesting that when adolescent patients have sexual health questions for providers, their parents might have those same questions as well (56).…”
Section: Therapeutic Partnershipmentioning
confidence: 99%
“…This knowledge contributes to the design of new interventions and to the readjustment of the services, as well as to designing projects and implementing actions, contributing to a better quality care. 20,[35][36] The use of information and communication technologies directed to health care is considered promising as it enables self-care and encourages healthy habits, information exchange and emotional support. Among these technologies, the phone is highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…By examining the role of parents, exchange, and kinship networks this study serves as an important step in advancing our knowledge of adolescent and young adult healthcare utilization in Ethiopia and beyond. In a recent article on parent and adolescent health communication, Ford et al () argued that “Patient‐centered health care recognizes that adolescents and parents are stakeholders in adolescent health” (p. 154, emphasis added).…”
Section: Discussionmentioning
confidence: 99%